Analisis Penggunaan Klausa Bebas dan Klausa Terikat dalam Cerpen “Hujan Kemarin” Karya Melissa Amelia Putri - Hidayat, Gilang Ramadhan Putra; Nurhaliza, Kamila; Aprilianti, Mayang; Sitaresmi, Nunung (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research aims to describe the use of free clauses and bound clauses in a short story entitled “Hujan Kemarin” by Melissa Amelia Putri published on Kompas website. This is done to find marker characteristics that can distinguish between independent clauses and dependent clauses. The method used in this research is descriptive-qualitative method using content analysis. Sampling in this research analysis uses purposive sampling. Based on the results of the analysis, the following conclusions can be drawn: there are 14 representative sentences as the analysis material in which there are independent clauses and dependent clauses. The function of the dependent clauses in a sentence can be S, O, Pel, and K and can be located in front or behind the independent clauses. Keywords: syntax, clause, short story